2013
DOI: 10.1093/cercor/bht015
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intrahemispheric Connectivity Differences When Reading Japanese Kanji and Hiragana

Abstract: Unlike most languages that are written using a single script, Japanese uses multiple scripts including morphographic Kanji and syllabographic Hiragana and Katakana. Here, we used functional magnetic resonance imaging with dynamic causal modeling to investigate competing theories regarding the neural processing of Kanji and Hiragana during a visual lexical decision task. First, a bilateral model investigated interhemispheric connectivity between ventral occipito–temporal (vOT) cortex and Broca's area (“pars ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Several studies have used dynamic causal modeling (DCM) of fMRI data to distinguish directed excitatory and inhibitory interactions from the blood oxygen level‐dependent (BOLD) signal present in different regions. These studies have reported predominantly excitatory interactions in posterior regions (Stephan et al, ; Carreiras et al, ; Kawabata‐Duncan et al, ; Bitan, Lifshitz, Breznitz, & Booth, ). These findings are consistent with the results of the current study, in which all observed instances of increased connectivity between the ROIs seem to reflect excitatory transmission of information rather than suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used dynamic causal modeling (DCM) of fMRI data to distinguish directed excitatory and inhibitory interactions from the blood oxygen level‐dependent (BOLD) signal present in different regions. These studies have reported predominantly excitatory interactions in posterior regions (Stephan et al, ; Carreiras et al, ; Kawabata‐Duncan et al, ; Bitan, Lifshitz, Breznitz, & Booth, ). These findings are consistent with the results of the current study, in which all observed instances of increased connectivity between the ROIs seem to reflect excitatory transmission of information rather than suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Seghier, Josse, Leff, and Price () reported asymmetrical left‐to‐right inhibitory interactions between dorsal frontal regions during semantic decision tasks on words and pictures. Kawabata‐Duncan et al () examining reading of Japanese kanji and kana characters, reported excitatory interactions among bilateral posterior regions, but right‐to‐left inhibition between IFGs. Thus, it is possible that the asymmetrical behavioral disruption of LVF‐rh stimuli under conditions of bilateral display may relate to a transcallosal inhibitory process in more anterior areas that would require a different experimental design to detect it using MEG.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke patients who have been afflicted by left hemisphere or bilateral lesions often have aphasia, indicating that the language‐related areas of the brain seem to show left hemisphere dominance (Laska, Hellblom, Murray, Kahan, & Von Arbin, ; Pedersen, Jørgensen, Nakayama, Raaschou, & Olsen, ). Hiragana Japanese script reading is also processed in the dorsal reading pathway in the left hemisphere, including the primary visual cortex, supramarginal gyrus, and Broca's area (Kawabata Duncan et al., ). In ERP studies, language‐related activation was found in a contingent negative variation (CNV) study, which revealed left hemisphere activation when a language task was used (Spironelli & Angrilli, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Price (2010) in a review of 100 language fMRI studies points towards a role of parietal areas in semantic retrieval especially when comprehension is more taxing at the perceptual or semantic level. Finally, more recently, Kawabata Duncan et al (2013) found increased connectivity between Broca's area and the supramarginal gyrus (area 40) in the left hemisphere when processing syllabographic Hiragana scripts, pointing again to the connections between these two language areas.…”
Section: Discussionmentioning
confidence: 92%
“…Several functional imaging studies have reported increased activity in the IPL area 40 in lexico-semantic processing (Demonet et al, 1992;Kawabata Duncan et al, 2013;Price, 2010). For example, Demonet et al (1992) in an early study using PET compared activations during a phonological and a lexico-semantic task and found differential activations in area 40 in the left hemisphere only during the lexico-semantic task.…”
Section: Discussionmentioning
confidence: 99%